IDENTIFIKASI JENIS DAN POTENSI BAMBU (Bambusasp.) SEBAGAI SENYAWA ANTIMALARIA - Agus Sujarwanta; Suharno Zen (Bioedukasi Jurnal Pendidikan Biologi, 2020)
Malaria is still a health problem in Indonesia caused by the protozoan genus Plasmodium through the bite of the Anopheles mosquito. One of the plants that can also be used to treat fever caused by parasitic diseases is bamboo (Bambusa sp.). The purpose of this research is to identify the type and potential of bamboo as an antimalarial compound in Lampung Province. This research be able to provide an overview of the diversity of bamboo species and their potential as an antimalaria compound in Lampung Provincein May-July 2020. Primary data collection methods were obtained directly in the field including bamboo stands, both growing wild and cultivating, and describing them. Morphological observations for identification such as rhizome root types; bamboo shoots; branching; culm; leaf; stem; and segments refer to the criteria used by Widjaja (1997). The data is analyzed descriptively and tabulated. The results obtained 14 species of bamboo consisting of 5 genera with 14 species: Gigantochloa robusta, Schizostachyum brachycladum (Kurz), Schizostachyum blumei, Gigantochloa atroviolacea, Gigantochloa pseudoarundinacea (Steud.), Bambusa vulgaris var. striata (Lodd.ex Lindl.), Gigantochloa apus (Kurz), Dendrocalamus strictus, Bambusa maculate (Widjaja), Bambusa glaucophylla (Widjaja), Dendrocalamus asper (Backer ex K. Heyne), Dinochloa scandens (Blume ex Nees Kuntze), Bambusa glaucophylla (Widjaja), Dendrocalamus asper (Backer ex K. Heey), Dinochloa scandens (Blume ex Nees Kuntze), Bambusa multiplex (Lour.) Raeusch. Ex Schult and Bambusa blumeana (Schult.f). Bamboo has the potential for crafts, construction, food, medicine (bamboo shoots from Bambusa vulgaris var. Striata, Gigantochloa apus leaves and water from Dinochloa scandens bamboo stems).Kata kunci: antimalarial,bamboo